Detail in contemporary retail design - Plunkett, Drew; Reid, Olga (London Laurence King, 2012)
"This book features 44 of the best recent examples of retail design from around the world, and examines the details within the larger decorative schemes. The examples range from specialist boutiques to branded high street chain stores, from fashion retailers to furniture shops and eateries, and include descriptive text, colour photographs, floor plans and sections, as well as numerous construction and decorative details."--Book Jacket
1. Introduction -- 2. Accessories -- 3. Clothing -- 4. Food & household -- 5. Footwear
Keywords: Stores, Retail -- Designs and plans; Store decoration; Interior architecture